Preregistration house officers in the four Thames regions: I. Survey of education and workload. - Dent, T H (1990)
OBJECTIVE--To assess the education and workload of preregistration house officers in the four Thames regions. DESIGN--Postal questionnaire. SETTING--Teaching and non-teaching hospitals in the four Thames regions. PARTICIPANTS--1064 Preregistration house officers. RESULTS--Response rate was 70% (740 replies). Nine per cent of house officers (66/729) worked a rota of one in two. The average house officer had 20.4 inpatients under his or her care and admitted 23.2 patients per week. Sixty two per cent of house officers (459/740) felt that they spent an excessive amount of time on non-medical tasks of no educational merit; 75% (546/725) had never received adequate guidance on breaking bad news and 64% (467/729) had never received adequate guidance on pain control; 34% (249/731) did not feel confident that they could perform cardiopulmonary resuscitation unsupervised. House officers would tend to recommend their post to a friend. CONCLUSIONS--There are deficiencies in preregistration training in the four Thames regions. The General Medical Council's requirements are not being heeded.